ANTIOXIDANT ACTIVITY OF PETAI SELONG (Leucaena leucocephala) USING DPPH (1,1 diphenyl-2-picrylhydrazl) - Saddam Husein; Erika Indah Safitri; Yovita Endah Lestari (Jurnal Farmasi Malahayati (JFM), 2022)
Petai selong or petai china (leucaena leucocephala) is populary consumed in southeast asia, such as indonesia, thailand, the philippines and malaysia. This paper aims to anlayze the antioxidant activity of petai selong (leucaena leucocephala) using DPPH(1,1 diphenyl-2-picrylhydrazl). The antioxidant activity is shown from the phytochemical analysis, degradation of DPPH, and kinetics degradation. Phytochemical analysis was carried out by dripping petai selong extract with various reagent.DPPH was conducted by mixing the DPPH and extract petai selong with 8 ppm, 12 ppm, 16 ppm, 20 ppm, and 24 ppm. The degradation analysis was conduted using spectrofotometer UV-Vis, and the kinetics degradation were calculated using Langmuir Hinshelwood (L-H). The results show that the petai selong has an antioxidant acitivty. It is stated that the highest degradation occurs at 24 ppm where it degrades about 10 ppm of DPPH, or approximatly about96.14 percent, and the lowest degradation occurs at 8 ppm where it degrades about 2 ppm of DPPH, or approximatly about 0.98 percent. The Langmuir Hinselwood calculations show that the kinetics degradations of DPPH increase with petai selong concentration. It is stated that the higher of petai selong concentrations, the higher of antioxidant effect.